Playing God : redeeming the gift of power - Crouch, Andy. (Downers Grove, Illinois : IVP Books, 2013)
Andy Crouch unpacks the dynamics of power that either can make human flourishing possible or can destroy the image of God in people. While the effects of power are often very evident, he uncovers why power is frequently hidden. He considers not just its personal side but the important ways power develops and resides in institutions. --from publisher description
The discovery of power -- The gift of power: in the beginning it was not so. Power is a gift -- Idolatry -- Injustice -- Icons -- The grip of power: it will not be so among you. The hiddenness of power -- Force, coercion and violence -- The lure of privilege -- Institutions and creative power: from generation to generation. The gift of institutions -- Principalities, powers and broken institutions -- Becoming trustees -- The end of power: we had to celebrate. Disciplined power -- The Sabbath leader -- The end of power.
Includes bibliographical references (pages 283-288) .
Description based on print version record.
Keywords: Power (Christian theology); RELIGION / Christian Life / Social Issues; RELIGION / Christianity / General; Electronic books